Hubungan Antara Indeks Massa Tubuh (IMT) Dengan Dismenorea Pada Remaja Putri Di Cilacap - Sujianti Sujianti; Ahmad Subandi (KOLONI, 2026)
Dysmenorrhea is pain or cramping that occurs during menstruation. It is a common gynecological disorder that can disrupt daily activities for most women. The primary cause of dysmenorrhea is strong uterine contractions aimed at expelling the unfertilized uterine lining. This study aims to determine the relationship of Body Mass Index (BMI) with dysmenorrhea in young women at Al Irsyad Islamic Junior High School, Cilacap. This research is quantitative with a cross sectional analytical design using primary data. The sample used were 54 young women taken using the total sampling technique. Data collection was conducted through a Food Frequency Questionnaire and secondary data from the most recent weight and height measurements. Data analysis used univariate analysis and Spearman rank analysis. The results showed a Spearman rank analysis p-value of > 0.05 (0.160). Conclusion: There is no corellation between BMI and dysmenorrhea in young women at Al Irsyad Islamic Junior High School, Cilacap.